The Effect of Fix Up Strategy in Enhancing Students’ Reading Comprehension in IAIN Curup - Suhermanto, Hadi (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This study aimed to find out whether there is any effect of fix-up strategy on students’ reading comprehension at second semester English Study Program students in IAIN Curup. This study employed a quasi experimental research design. The sample of this study was second semester English Study Program students in IAIN Curup. It consisted of 60 students. The instrument on this research was reading test which was aimed to measure students’ reading comprehension. The reading test consists of 30 multiple choice questions for pre-and post-test. The finding of this research showed that the t-count value was 3,905 more than t-table value, it means that H0 was rejected and hypothesis H1 that stated there was any effect of applying fix-up strategy on the students’ reading comprehension at second semester English Study Program students in IAIN Curup was accepted. Fix-up strategy was proved to be effective to be used in teaching reading since there was a significant difference of students’ meanscore after doing the treatment by using fix-up strategy. Key words: Reading Comprehension, Fix-Up Strategy